(untitled) (Andamios, Revista de Investigación Social, 2025)
This article explores the convergence between neoliberal ethopolitics and the discourse of modern managerial stoicism. Considering neoliberalism as “governmentality”—that is, as a political technology that lays on certain forms of subjectivity—we will explore how the Stoic revival fits with and reinforces the individualistic, competitive, and hierarchical impulses of our time. Thus, we seek to contribute to the development of a political-conceptual cartography that attends to its expansive and entrepreneurial variants as well as to that reactionary neoliberalism that seeks to articulate the corrosive forces of the market and traditional values.